Characteristics analysis of 157 cases of central airway stenosis due to tracheobronchial tuberculosis: A descriptive study - Zhuang, Rongjuan; Yang, Mingjin; Xu, Li; Li, Yishi; Li, Ying; Hu, Tingting; Chen, Yan; Nie, Xiao; Yan, Xiaofeng; Kong, Xianghua; Yang, Song; Guo, Shuliang (Frontiers in Public Health, 2023)
Background: Tracheobronchial stenosis, particularly central airway stenosis, which frequently results in severe complications such as lung damage, occurs in patients with tracheobronchial tuberculosis (TBTB). Objectives: To analyze the clinical characteristics of patients with central airway stenosis due to tuberculosis (CASTB). Methods: Retrospective analysis was performed on the clinical features, radiological features, bronchoscopic features and treatment of 157 patients who were diagnosed with CASTB at the First Affiliated Hospital of Chongqing and the Public Health Medical Center, from May 2020 to May 2022. Results: CASTB mostly occurs in young patients and in females. Patients with CASTB exhibited different symptoms repeatedly during the course of disease, especially varying degrees of dyspnea, prompting many patients to undergo bronchoscopic airway intervention and even surgery. Patients with cicatricial strictures constituted the highest proportion of TBTB subtype with CASTB and 35.7% of the patients with CASTB were found to have tracheobronchomalacia (TBM) under bronchoscopy. CASTB and TBM mainly involved the left main bronchus. Patients with lower level of education had higher rates of TBM. Patients with TBM manifested shortness of breath more frequently than patients without TBM.Bronchoscopic intervention probably promoted the development of TBM. Conclusions: CASTB is more likely to affect young and female population, accompanied by different symptoms especially varying degrees of dyspnea. Despite mostly adequate anti-tuberculosis chemotherapy, patients with CASTB present with severe scarring stenosis, bronchial occlusion, malacia and even destroyed lung.